Robot-assisted radical cystectomy with intracorporeal reconstruction of urinary diversion by mechanical stapler: prospective evaluation of early and late complications - Cochetti, Giovanni; Paladini, Alessio; Del Zingaro, Michele; Ciarletti, Sara; Pastore, Francesca; Massa, Guido; De Angelis, Lorenzo; Mearini, Ettore (Frontiers in Surgery, 2023)
Radical cystectomy with pelvic lymph node dissection is the gold standard treatment for non-metastatic muscle invasive bladder cancer and high risk non muscle invasive bladder cancer. For years, the traditional open surgery approach was the only viable option. The widespread of robotic surgery led to its employment also in radical cystectomy to reduce complication rate and to improve the functional outcomes. Regardless of type of approach, radical cystectomy is a procedure with high morbidity and not negligible mortality. Data available in the Literature show how the use of staplers can offer valid functional outcomes, with acceptable rate of complications shortening the operative time. Aim of our study was to describe the perioperative outcomes and complications associated with robotic radical cystectomy (RARC) with intracorporeal urinary diversion (ICUD) using mechanical stapler. Material and Methods From January 2015 to May 2021, we enrolled patients underwent RARC with pelvic node dissection and stapled ICUD (ileal conduit or ileal Y-shaped neobladder according to the Perugia ileal neobladder) in our high-volume center. Demographic features, peri-operative outcomes, early (≤ 30 days) and late (> 90 days) post-operative complications according to the Clavien-Dindo classification, were recorded for each patient. We also analysed the potential linear correlation between demographic, pre-operative as well as operative features and the risk of post-operative complications. Results Overall, 112 patients underwent RARC with ICUD were included with minimum follow-up of 12 months. Intracorporeal Perugia ileal neobladder was performed in 74.1% of cases while ileal conduit was performed in 25.9%. Mean operative time, estimated intraoperative blood loss and LOS were 289.159.7 minutes, 390.6186.2 ml and 17.59.8 days, respectively. Early minor and major complications accounted for 26.7% and 10.8%, respectively. Overall late complications were 40.2%. The late most common complications were hydronephrosis (11.6%) and urinary tract infections (20.5%). Stone reservoirs formation occurred in 2,7% of patients. Major complications occurred in 5.4%. In the sub-analysis the mean operative time and the estimated blood loss improved significantly from the first 56 procedures to the last ones. Conclusion RARC with ICUD performed by mechanical stapler is a safe and effective technique. Stapled Y-shaped neobladder did not increase complication rate.